Review of Three DNA Analysis Applications for Use in the Microbiology or Genetics Classroom - David S. Treves (American Society for Microbiology, 2010)
Review of: three widely used DNA analysis programs. Two of these (Chromas and Finch TV) are simple viewing and editing applications. The third (MEGA) also allows for viewing and editing but “ups the ante” considerably in terms of power in DNA data analysis. In evaluating these applications, special consideration was given to how easily an imported DNA sequence could be viewed, edited and submitted to GenBank using BLAST.